Chronic Cocaine Use and Its Association With Myocardial Steatosis Evaluated by 1H Magnetic Resonance Spectroscopy in African Americans. Issue 1 (January 2015) - Lai, Shenghan; Gerstenblith, Gary; Li, Ji; Zhu, Hong; Bluemke, David A.; Liu, Chia-Ying; Zimmerman, Stefan L.; Chen, Shaoguang; Lai, Hong; Treisman, Glenn
<x xml:space="preserve">Abstract</x> Objectives: Cardiac steatosis is a manifestation of ectopic fat deposition and is associated with obesity. The impact of chronic cocaine use on obesity measures and on the relationship between obesity measures and cardiac steatosis is not well-characterized. The objectives of this study were to compare obesity measures in chronic cocaine users and nonusers, and to explore which factors, in addition to obesity measures, are associated with myocardial triglyceride in African Americans, using noninvasive magnetic resonance spectroscopy. Methods: Between June 2004 and January 2014, 180 healthy African American adults without HIV infection, hypertension, and diabetes were enrolled in an observational proton magnetic resonance spectroscopy and imaging study investigating factors associated with cardiac steatosis. Results: Among these 180 participants, 80 were chronic cocaine users and 100 were nonusers. The median age was 42 (interquartile range, 34-47) years. Obesity measures trended higher in cocaine users than in nonusers. The median myocardial triglyceride was 0.6% (interquartile range, 0.4%-1.1%). Among the factors investigated, years of cocaine use, leptin, and visceral fat were independently associated with myocardial triglyceride. Body mass index and visceral fat, which were significantly associated with myocardial triglyceride in noncocaine users, were not associated with myocardial triglyceride content in cocaine users. Conclusions: This study shows (1) cocaine users may have more fat than nonusers and (2) myocardial triglyceride is independently associated with duration of cocaine use, leptin, and visceral fat in all subjects, whereas leptin and high-density lipoprotein cholesterol, but not visceral fat or body mass index, in cocaine users, suggesting that chronic cocaine use may modify the relationships between obesity measures and myocardial triglyceride.